2022
DOI: 10.3390/electronics11111751
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Graded-Reading Websites/Applications on EFL Undergraduates’ Reading Comprehension during COVID-19 Pandemic

Abstract: The COVID-19 pandemic has resulted in many educational changes, especially the shift towards the use of technology in all subjects. This longitudinal study was conducted to investigate the effect of learning environments—blended and online, alone and with graded-reading websites/applications—on the reading comprehension of Saudi undergraduates majoring in English during COVID-19 pandemic. In this study, 130 participants were selected (control: male [N = 21], female [N = 54]; or experimental: male [N = 21], fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Indonesian EFL learners who prepared well for this competition had good pronunciation to deliver the storytelling. Alghizzi &Elyas (2022), andHibatullah (2019) agreed that practicing more perfectly, is one of the ways to overcome the challenges in EFL classes practicing the English language frequently. On the other hand, Irma (2020) stated that all problems in English specifically faced by EFL learners can arise from the learners themselves.…”
Section: Resultsmentioning
confidence: 99%
“…The Indonesian EFL learners who prepared well for this competition had good pronunciation to deliver the storytelling. Alghizzi &Elyas (2022), andHibatullah (2019) agreed that practicing more perfectly, is one of the ways to overcome the challenges in EFL classes practicing the English language frequently. On the other hand, Irma (2020) stated that all problems in English specifically faced by EFL learners can arise from the learners themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Although the impacts of roughly-tuned EFL learning materials, such as the passages examined in the present study, on the student's mastery of English may vary from one context to another and depend on the student's English proficiency, studies on the effect of graded readers on the students' reading comprehension (e.g. Kara,2019;Chou, 2022;Hagley, 2017;Alghizzi & Elyas 2022) showed that those who were exposed to graded readers performed better than those who were not. To some extent, the finding of these research re-proved the importance of the concept comprehensible input (Krashen,1982) in language teaching and learning which stresses that, in order for learning to take place successfully, language learners should be exposed to input (spoken or written language) that is at or slightly above their present level of language ability.…”
Section: Discussionmentioning
confidence: 97%
“…Woltran et al [4] studied Christensen and Knezek's theoretical Will-Skill-Tool model to examine various factors that influenced teachers' use of digital technologies during remote emergency education due to the materialization of COVID-19 in the spring of 2020. Alghizzi and Elyas [5] conducted a study to analyze the effect of learning environments (blended and online) on the reading comprehension in English of Saudi undergraduates during the COVID-19 pandemic. Sucuo glu and Andrew [6] presented a paper investigating the impact of adopting e-learning to fix the dilapidated Nigerian educational structure.…”
Section: The Present Issuementioning
confidence: 99%